Macroscopic architecture of covalent organic frameworks for storage and purification - Khayum M, Abdul (CSIR-National Chemical Laboratory, Pune, 2019)
The research on porous materials gain increasing attention due to their potential properties in various fields like gas storage; catalysis; energy storage; sensors; drug-delivery; opto-electronics etc. The recent research interest on porous materials mostly associated with the design of 2D or 3D symmetrical porous polymers, i.e., crystalline polymers like metal organic frameworks (MOFs); covalent organic frameworks (COFs); hydrogen bonded organic frameworks (HOFs) etc. Among these, COFs are very well known for their 2D/3D crystallinity; tunable porosity; low-density; and chemical and thermal stabilities. As a result of their exceptional structural features, COFs were well investigated for storage of valuable gases like H2, NH3, CO2; heterogeneous catalysis; electrode material in energy storage devices; and water purification applications. However, the typical unprocessable granular form of COFs obstructs the leverage of material into the technologically relevant macroscopic forms like two-dimensional (2D) thin films, sheets and three-dimensional (3D) architectures. Meanwhile, the notable researches on the macroscopic architecture of alike materials such as graphene, carbon nanotubes, polymer gels etc delivered the outstanding output of the properties in various applications. In this regard, it is to be expected that the 2D or 3D macroscopic engineering of COFs can provide a new dimension of the scientific and commercial aspects of the material. Moreover, the advanced exploration of electrochemical energy storage demands flexible 2D- thin sheet with mechanical robustness and electrical conductivity. Additionally, scientist look forward to the development of 3D architecture aerogel of crystalline porous polymers which has paramount importance in adsorption based micro-pollutant purification of water.
Keywords: Natural Sciences